A low frequency 3D lightning mapping network in north China - Ma, Zilong; Jiang, Rubin; Qie, Xiushu; Xing, Hongyan; Liu, Mingyuan; Sun, Zhuling; Qin, Zilong; Zhang, Hongbo; Li, Xiao (Atmospheric research, 2021)
A 3D low-frequency lightning mapping network with eight stations is deployed in the SHAndong Triggering Lightning Experiment (SHATLE) in north China. The ABA (A, B double time base) data acquisition system based on first input first output memory is adopted. The effective and stable acquisition of electromagnetic radiation data from lightning is realized by designing real-time monitoring of the acquisition speed. The accuracy of the time of the data is ensured using a double timestamp scheme. Noise pulse analysis is integrated to effectively solve the adverse effects of the background noise during the 3D location of the lightning radiation sources. According to the error distribution obtained by Monte Carlo estimation, the horizontal location errors are <200 m in the coverage area of the network. The ground truth calibration based on six return strokes of a triggered lightning flash gives an average horizontal error of 104.9 m. The details of development of both the cloud-to-ground lightning flash and the intracloud lightning flash can be clearly mapped in the 3D location. To reduce the influence of the zig-zag development of lightning on the estimation of propagation speed, a method to calculate the 3D propagation speed of the lightning branch based on the Density-Based Spatial Clustering of Applications with Noise (DBSCAN) clustering algorithm is proposed. The accuracy of the estimated 3D development speed of the lightning branch is improved by the proposed method. •A high-precision 3D low-frequency lightning location system is built in north China.•Stable data acquisition system is designed with double time base scheme embedded.•Density-based clustering method is developed to discern branches and calculate speeds.